Meiofauna in the southeastern Bering Sea: community composition and structuring environmental factors - Tachibana, Kazuki; Shimanaga, Motohiro; Langlet, Dewi; Seike, Koji; Miyazaki, Masayuki; Yoshida, Mitsuhiro; Nunoura, Takuro; Nomaki, Hidetaka (Frontiers in Marine Science, 2023)
The Bering Sea is the second largest marginal sea in the North Pacific and is one of the areas with highest biological productivity in high-latitude waters. The continental shelf of the Bering Sea hosts large populations of marine mammals and fishery resources. However, the smaller organisms in benthic ecosystems, including meiofauna, have been largely overlooked in this area, despite their potential importance in ecosystem functioning and the resultant biogeochemical cycles. This study analyzed spatial differences in the total abundance and community structure of the metazoan meiofauna at five stations around the Bering Canyon, located at the southeastern margin of the Bering Sea. Their association with environmental factors in sediments was also studied. The results confirmed that the investigated stations had meiofaunal standing stocks that were comparable to those of other Arctic seas. Among the investigated sediment biological and geochemical parameters (total organic carbon, median grain size, prokaryotic cell numbers, etc.), multivariate analyses showed that the C/N of organic matter in sediments was the main factor associated with meiofaunal community structure.